2013
DOI: 10.1007/s11434-013-5730-5
|View full text |Cite
|
Sign up to set email alerts
|

Delayed drainage of aquitard in response to sudden change in groundwater level in adjacent confined aquifer: Analytical and experimental studies

Abstract: The problem of the groundwater dynamics and water balance of a confined aquifer in the aquifer system has been solved in previous studies, whereas that in the aquitard adjacent to the confined aquifer has seldom been considered. In reality, the groundwater dynamics of the aquitard are closely related to the exploitation of groundwater resources, groundwater contamination, underground storage utilization and land subsidence. In this paper, an analytical solution is derived to describe the drawdown variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…The process of groundwater being released or stored is accompanied by compressive or rebound deformation and the change in the volume of storage in the aquitard is equal to its deformation (Konikow and Neuzil ). Based on the water balance equation of Zhou et al (), the dimensionless aquitard deformation F eD caused by s ewD is derived as FnormalenormalD()teD=normalRnormale0.25em[]normalcosh()α1αnormalsinh()αnormalexp()α2tnormalenormalD and the corresponding dimensional form of F eD is expressed as Fe=FnormalenormalDAnormalenormalwSnormalsnormalknormaleb where Re denotes the real part of the complex expression, α=2πitrue/TnormalenormalD and i=1. Details concerning the derivation of Equation are provided in Appendix S1 of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The process of groundwater being released or stored is accompanied by compressive or rebound deformation and the change in the volume of storage in the aquitard is equal to its deformation (Konikow and Neuzil ). Based on the water balance equation of Zhou et al (), the dimensionless aquitard deformation F eD caused by s ewD is derived as FnormalenormalD()teD=normalRnormale0.25em[]normalcosh()α1αnormalsinh()αnormalexp()α2tnormalenormalD and the corresponding dimensional form of F eD is expressed as Fe=FnormalenormalDAnormalenormalwSnormalsnormalknormaleb where Re denotes the real part of the complex expression, α=2πitrue/TnormalenormalD and i=1. Details concerning the derivation of Equation are provided in Appendix S1 of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The results from a viscoelastic model developed to simulate one-dimensional consolidation showed that land subsidence obviously lags behind pore pressure disappearance [16]. In addition, the lag time of the clay layer deformation was in direct proportion to the thickness of the layer [17,18]. The delay index is only dependent on the properties and thickness of the aquitard in response to the sudden change in groundwater level in adjacent confined aquifers according to experimental studies [19].…”
Section: Introductionmentioning
confidence: 99%
“…Alluvial plains and sedimentary basins are often composed of a number of relatively high-permeability aquifers alternating with relatively low-permeability aquitards (Cihan et al 2011;Hantush 1967). These aquifers and aquitards often extend over large areas, even covering entire basins or alluvial plains, such as in the Dakota aquifer system in South Dakota in the United States and the Yangtze Delta in China (Cihan et al 2011;Konikow and Neuzil 2007;Zhou et al 2013). Groundwater depletion is the inevitable and natural consequence of withdrawing water from an aquifer (Konikow and Kendy 2005), and the water stored in aquitards is a significant source of water to pumped aquifers (Hantush 1960;Neuman and Witherspoon 1969a, b).…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all of these studies used models that were not influenced by previous pumping history and assumed that the drawdown in the aquitards was zero. As a result, these models are not applicable to aquitards influenced by DYP, which causes disequilibrium owing to previous changes in the water level of aquifers adjacent to an aquitard (Neuman 1979;Zhou et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation